Determinants of Financial Management Behavior Among Generation Z University Students in Kupang: The Role of Financial Literacy, Financial Technology Adoption, and Financial Self-Efficacy - Wihelmina Muni; Septia S. Dioh; Taqwa Sultan; Moni Y. Siahaan; Yanti S. Giri (CV. Jala Berkat Abadi, 2026)
This study examines the determinants of financial management behavior among Generation Z university students in Kupang City by integrating financial literacy, financial technology adoption, and financial self-efficacy within the Theory of Planned Behavior framework. A quantitative explanatory design was employed using survey data from 218 students, analyzed through PLS-SEM. The findings reveal that financial literacy, fintech adoption, and financial self-efficacy significantly influence financial management behavior, both individually and simultaneously. Financial literacy serves as the primary cognitive foundation, self-efficacy strengthens perceived behavioral control, while fintech functions as an enabling contextual factor rather than a deterministic driver. The model demonstrates moderate predictive power, indicating that responsible financial behavior among Gen Z students emerges from the interaction of cognitive, psychological, and technological dimensions. This study contributes to extending behavioral finance research in emerging regional contexts and highlights the need for integrative financial education strategies in higher education institutions.